Racial Bias in The Adaptation of Rumaan Alam’s Novel Leave The World Behind into Film by Sam Esmail - Hanifah Nur Rohmah; Hat Pujiati (Haluan Sastra Budaya, 2025)
This study is the publication version of a thesis entitled the same as this article which analyzes the influence of the changes in racial bias representation that occur in the film adaptation Leave the World Behind. Explores the transformation of racial bias as depicted in Rumaan Alam’s novel Leave the World Behind (2020) and its film adaptation by Sam Esmail (2023). It applied the theory of adaptation proposed by Linda Hutcheon and the qualitative method to analyze the narrative events, characters and characterization, and plot changes between the novel and film. The results indicate that while the novel subtly explores implicit racial bias, the film intensifies and recontextualizes these tensions through visual storytelling. In Leave the World Behind film introduces reversed racial bias and character developments that reflect broader socio-political discourse, partly driven by economic lures, political, and cultural capital motives. This paper aims to highlight specific changes in two different media and uncover the motives behind them.